Unveiling tolerance mechanisms in pepper to combined low-temperature and low-light stress: a physiological and transcriptomic approach - Jie Zhang; Hamza Sohail; Xuewen Xu; Yongtai Zhang; Yongji Zhang; Yibo Chen (BMC Plant Biology)
Abstract Background Pepper (Capsicum annuum L.) is a vegetable crop of significant economic importance, but its yield and quality are severely affected by the combined stress of low temperature and low light (LL), particularly in greenhouse environments. Despite this, the physiological and molecular mechanisms underlying pepper’s response to LL stress remain poorly understood. In this study, we conducted physiological and transcriptomic analyses on two pepper genotypes: Y2, a LL-sensitive genotype, and Y425, a LL-tolerant genotype. These genotypes were subjected to LL stress conditions (10 °C/5°C, 100 µmol m⁻²s⁻¹) and control (CK) conditions (28 °C/18°C, 300 µmol m⁻²s⁻¹). Results Three days after treatment, the phenotypes of the two pepper genotypes began to show clear distinctions, with Y425 seedlings exhibiting greater root length, shoot fresh weight, and root fresh weight compared to Y2. Additionally, comparative transcriptome analysis of leaf samples from both genotypes identified a total of 13,190 differentially expressed genes (DEGs). Gene Ontology (GO) enrichment analysis revealed that genes associated with photosynthesis, osmotic stress response, reactive oxygen species response, and other GO terms potentially contribute to LL tolerance. Moreover, three key pathways involved in the response to LL stress were identified: photosynthesis-antenna proteins, zeatin biosynthesis, and circadian rhythm pathways. The key DEGs in these pathways were expressed at higher levels in Y425 as compared with Y2. Furthermore, physiological indicators such as chlorophyll fluorescence parameters, chlorophyll content, osmoregulatory substances, and antioxidant enzyme activities decreased under LL stress; however, the reduction was significantly greater in Y2 compared to Y425, further validating the molecular findings from the transcriptome analysis. Conclusion This study identified significant physiological and transcriptomic differences in two pepper genotypes under LL stress. It highlighted key pathways and provide novel insights into the molecular and physiological mechanisms of pepper’s LL tolerance. These results emphasize the importance of optimizing greenhouse conditions for better crop productivity.